2012
DOI: 10.5194/bg-9-2325-2012
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon storage changes in coastal wetlands of the modern Yellow River Delta from 2000 to 2009

Abstract: Abstract. Soil carbon sequestration plays an essential role in mitigating atmospheric CO 2 increases and the subsequently global greenhouse effect. The storages and dynamics of soil organic carbon (SOC) of 0-30 cm soil depth in different landscape types including beaches, reservoir and pond, reed wetland, forest wetland, bush wetland, farmland, building land, bare land (severe saline land) and salt field in the modern Yellow River Delta (YRD) were studied based on the data of the regional survey and laboratory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 44 publications
2
46
2
Order By: Relevance
“…The storage and distribution heterogeneity of SOC depend on climate conditions (Davidson and Janssens, 2006), land-use patterns (Poeplau and Don, 2013;Yu et al, 2012), and human activities and policies (Cao et al, 2011a(Cao et al, , 2011bHeikkinen et al, 2013;. The distribution of SOC has been correlated with various climate factors, soil texture, and land cover types (Batjes and Dijkshoorn, 1999;Jobbágy and Jackson, 2000;Li and Zhao, 2001;Saiz et al, 2012;Wang et al, 2004;Yang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The storage and distribution heterogeneity of SOC depend on climate conditions (Davidson and Janssens, 2006), land-use patterns (Poeplau and Don, 2013;Yu et al, 2012), and human activities and policies (Cao et al, 2011a(Cao et al, , 2011bHeikkinen et al, 2013;. The distribution of SOC has been correlated with various climate factors, soil texture, and land cover types (Batjes and Dijkshoorn, 1999;Jobbágy and Jackson, 2000;Li and Zhao, 2001;Saiz et al, 2012;Wang et al, 2004;Yang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The average estimation error of prediction using linear model was about 1.2%. The results of Wang et al (2009) showed that land use management and of soil type have the greatest impact on spatial variability of soil organic carbon.…”
Section: Model Evaluationmentioning
confidence: 94%
“…Plow direction 15 tillage With respect to the 3 management systems, the study area was delineated to 10*10 meters quadrates. The systematic random sampling (Yu et al, 2012) was performed in each quadrate. Soil samples from the 4 corners of the quadrates and their center were taken from depth of 0-30 cm (Stöckle et al, 2012) and mixed as a composite sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that the SOC content would be significantly increased with improved soil quality (i.e., salinity reduction) and agricultural management (i.e., freshwater addition). Yu et al (2012) claimed that the Yellow River Delta will have great potential for SOC sequestration because of its low SOC content compared to other coastal regions in China (Dodla et al 2008;Wang et al 2007); moreover, anthropogenic activities have played a major role in the SOC dynamics in this area.…”
Section: Soc Evolutions During the Last 30 Yearsmentioning
confidence: 99%